Analysis of Stock Prices Before and After the Pandemic on Banking in Indonesia - Heliani; Nurul Setia Rahayu; Randi; Rida Fitriana; Junaedi Siswanto (Nusantara Science and Technology Proceedings, 2020)
Covid-19 not only has an impact on the health sector but Covid-19 also has an impact on the economic sector in Indonesia. This study aimed to analyze how Covid- 19 affects the decline in share prices in Indonesian banks from before, at the peak and after Covid-19, the sample banks include the Asian Central Bank (BCA), Bank Rakyat Indonesia (BRI), Bank Negara Indonesia. (BNI) and Bank Mandiri. The stock price before Covid-19 was said to be quite stable, while at the peak of the pandemic, the price of sham had decreased which caused investors not to invest their funds because they were considered not profitable. Because with the emergence of the Covid19 pandemic, many banking companies in Indonesia experienced a very significant decline in share prices, a comparative analysis was carried out on the decline in share price value. so that the title of the determination this time is about Stock Price Analysis Before and After the Banking Pandemic in Indonesia. The research method used in this research is a qualitative research method that contains comparative analysis. In this determination, it was concluded that the Covid-19 pandemic could affect the level of supply and demand which resulted in a decrease in the value of share prices in each bank.